The Effect of Acute Ethanol Challenge on Global Visuospatial Attention: Exaggeration of Leftward Bias in Line Bisection - Leone, Lynnette (2009)
Acute alcohol challenge has been associated with a selective impairment of right hemisphere function. A hallmark of visuospatial neglect syndrome is that patients with right hemisphere lesions misbisect horizontal lines far rightward of veridical center. Neurologically intact subjects misbisect lines with a systematic leftward bias (pseudoneglect). Neuroimaging studies in neurologically intact subjects reveal predominant right hemisphere activation during performance of line bisection tasks. The current study assessed whether acute alcohol challenge alters global visuospatial attention. Subjects (N=18; 10 male; strongly right-handed; mean age=23 years) engaged in a forced-choice tachistoscopic line bisection task in both ethanol challenge (mean BAC=.077) and no ethanol control conditions. Mean leftward bisection error in the control challenge condition was −0.238 degrees visual angle (1.05% line length), and leftward bisection error significantly increased (p=.001) under ethanol challenge (−0.333 degrees visual angle, 1.47% line length). Mean bisection precision in the control condition was 0.358 degrees visual angle (1.58% line length); bisection precision significantly deteriorated (p=.008) under ethanol challenge (0.489 degrees, 2.17% line length). Decreased bisection precision indicates that ethanol disrupts the fidelity of visuospatial performance. The exaggerated leftward bisection error implies that ethanol may exert a differential effect on left versus right hemispheric function with respect to the control of global visuospatial attention.